Fatal Attractions, Abjection, and the Self in Literature from the Restoration to the Romantics - Alexander, Laura (Cambridge Scholars Publisher, 2019)
This book examines Julia Kristeva's theory of abjection in several works by early British writers from the Restoration to the Romantic era. This period saw an increased emphasis on understanding the self. Poems with anxious speakers or narratives featuring characters with considerable psychic pressures emerged as writers responded to ideas on consciousness by natural philosophers. The pursuit of self-knowledge also reached greater imaginative depths, inspiring new artistic movements, including sensibility, with its attention to expressions of the suffering self, and the Gothic, a mode of art that examines the self's deepest fears. Romantic writers theorized about artistic genius, creating a cult of the self that has never left us. Kristeva offers a more complete psychoanalytic vocabulary for understanding the self's unconscious motivations in literature written during this period, and this book provides readers interested in early British literature, philosophy, and literary theory with a constructive perspective for thinking about literary depictions of the self-in-crisis. Intro – Dedication – Table of Contents – Acknowledgments – Introduction – Chapter One – Chapter Two – Chapter Three – Chapter Four – Chapter Five – Chapter Six – Conclusion – Notes – Bibliography – Index.
Description based on publisher supplied metadata and other sources
Keywords: Psychoanalysis and literature..; Abjection in literature; Electronic books